Interfacial and Micellization Behavior of Cetyltrimethylammonium Bromide (CTAB) in Water and Methanol-Water Mixture at 298.15 to 323.15 K - Sujit Kumar Shah; Ajaya Bhattarai (Journal of Chemistry)
The micellization behavior of cetyltrimethylammonium bromide (CTAB) in water , 0.1, 0.2, 0.3, and 0.4 volume fractions of methanol at 298.15, 308.15, 318.15, and 323.15 K were investigated by surface tension measurements. The effect of methanol on values of critical micelle concentration (cmc), free energies of micellization ΔGmo, and surface properties viz. maximum surface excess concentration Γmax, area occupied by per surfactant molecule Amin, surface pressure πcmc, solution surface tension γcmc, solvent surface tension (γo), free energies of adsorption ΔGadso, the efficiency of adsorption (pC20), effective Gibbs free energy ΔGeffo, and free energy of surface at equilibrium (Gmin) were investigated using surface tension values. Other parameters such as the packing parameter (P), aggregation number (N), concentration of surfactant in the bulk phase (C20), relation between Amin and πcmc, and correlation of slopes dγ/d log C, γo/γcmc, Γ/Γmax, cmc/C20, ΔGadso/ΔGmo, and cmc/pC20 with the volume fraction of methanol are calculated and discussed in the light of the experiment done.